Beckman Saturn H2 Gas Detection System (1963)
This prototype polarographic hydrogen detector was developed by Beckman Instruments' Space Engineering Group (SEG) in 1963 for use in NASA's Saturn Rocket Program. This instrument measured the partial pressure of hydrogen in a gaseous mixture without depending on oxygen for the electro-chemical reaction. A different instrument -- an eight channel Hydrogen Monitor and Alarm System -- was ultimately created from this prototype and used for monitoring the Saturn rocket during fueling and launch.
Keywords: Scientific apparatus and instruments; Hydrogen--Measurement; Beckman Instruments, Inc.